2018
DOI: 10.2298/tsci170913018u
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a novel high performance induction air heater

Abstract: This study represents an experimental and numerical investigation of the enhanced prototypes of the induction air heaters. For this purpose, flow field is enhanced in order to avoid turbulence. The air mass flow rate, outlet construction and the application of insulation of the outer surface of the heater were selected as the performance enhancing parameters. Depending on the exit construction, the new designed prototypes are named as K-2 and K-3. Experiments were performed under two groups for three various f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In their experimentation of an air heater pool-type prototype, Unver et al indicated that they avoid turbulence as it increases the duration of air passing which has a negative effect on heat transfer [35].…”
Section: Turbulence Effect On Heating Timementioning
confidence: 99%
See 2 more Smart Citations
“…In their experimentation of an air heater pool-type prototype, Unver et al indicated that they avoid turbulence as it increases the duration of air passing which has a negative effect on heat transfer [35].…”
Section: Turbulence Effect On Heating Timementioning
confidence: 99%
“…Heat losses can be avoided with an appropriate insulation of steam tubes or containers [34], [35]. A variety of materials has been used for that including ceramic and borosilicate glass among others [13], [24].…”
Section: Water Heating Losses: Insulationmentioning
confidence: 99%
See 1 more Smart Citation